Health differences at birth between Roma and non-Roma children in Hungary: Long-run trends and decompositions - Tamás Hajdu; Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2017)
This paper uses birth records linked to census data to document health differences at birth between Roma and non-Roma children in Hungary between 1981 and 2010. It focuses on differences in average birth weight and average gestational age, as well as the likelihood of low birth weight and the likelihood of preterm birth. The paper shows large gaps in all indicators over the 30 years, with a small narrowing of the gap in absolute terms but not in relative terms. Roma mothers are twice as likely to give birth to babies with low birth weight and before the 37th week. Standard decompositions show that around 80% of the gap is explained by socioeconomic factors, and education alone explains more than half. Despite significant changes in society, the explanatory power of education and other factors remains constant. Narrowing the gap in educational attainment, especially at higher levels, may have the highest potential to improve the relative health of Roma births.
Keywords: I14; J15; 330; health at birth; birth weight; preterm birth; minorities